Pengaruh Perilaku Konsumen Terhadap Keputusan Pembelian Mahasiswa Angkatan 2022/2023 Fakultas Ekonomi dan Bisnis Islam (FEBI) Universitas Islam Negeri Fatmawati Sukarno (UINFAS) Bengkulu - Alnizam (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
ABSTRAK This study aims to analyze the influence of cultural, social, personal, and psychological factors on the purchasing decisions of students at the Faculty of Economics and Islamic Business (FEBI), UIN Fatmawati Sukarno Bengkulu, class of 2022/2023. Theoretically, consumers are considered rational agents who maximize utility; however, in practice, purchasing behavior is also influenced by psychological and social factors. This quantitative study employs a causal associative design and collects data through Likert-scale questionnaires distributed to 100 respondents. Data analysis uses multiple linear regression, t-tests for partial hypothesis testing, and F-tests for simultaneous hypothesis testing. The results show that all factors positively and significantly affect purchasing decisions, with personal factors being the most dominant. The regression model explains 65.5% of the variance in purchasing decisions. Implications of the study suggest marketers should personalize marketing content and emphasize the halal aspect of products in accordance with the Islamic values held by the students. Further research is recommended to explore additional external variables and employ mixed methods to better understand intrinsic motivations and Islamic values in consumer behavior.